An optimized mouse parabiosis protocol for investigation of aging and rejuvenative mechanisms - Rodriguez, Sonia L.; Carver, Chase M.; Dosch, Andrew J.; Huffman, Derek M.; Duke Boynton, Felicia D.; Ayasoufi, Katayoun; Schafer, Marissa J. (Frontiers in Aging, 2022)
Surgical parabiosis enables sharing of the circulating milieu between two organisms. This powerful model presents diverse complications based on age, strain, sex, and other experimental parameters. Here, we provide an optimized parabiosis protocol for the surgical union of two mice internally at the elbow and knee joints with continuous external joining of the skin. This protocol incorporates guidance and solutions to complications that can occur, particularly in aging studies, including non-cohesive pairing, variable anesthesia sensitivity, external and internal dehiscence, dehydration, and weight loss. We also offer a straightforward method for validating postoperative blood chimerism and confirming its time course using flow cytometry. Utilization of our optimized protocol can facilitate reproducible parabiosis experimentation to dynamically explore mechanisms of aging and rejuvenation.